1994
DOI: 10.2214/ajr.162.2.8310919
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of acute esophageal food impaction with glucagon, an effervescent agent, and water.

Abstract: OBJECTIVE.In i990, we described a combination therapy that uses glucagon, an effervescent agent, and water to relieve acute esophageal food impaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
2
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 8 publications
0
14
2
1
Order By: Relevance
“…Thimmapuran et al [5] found that glucagon was effective in 33 % of 125 cases. A smaller study found that glucagon and an effervescent drink were effective in 69 % of cases [6]. Our study suggests that the cost of a glucagon strategy is significantly lower than an initial endoscopy strategy.…”
Section: Discussionmentioning
confidence: 57%
“…Thimmapuran et al [5] found that glucagon was effective in 33 % of 125 cases. A smaller study found that glucagon and an effervescent drink were effective in 69 % of cases [6]. Our study suggests that the cost of a glucagon strategy is significantly lower than an initial endoscopy strategy.…”
Section: Discussionmentioning
confidence: 57%
“…Et ve benzeri ÖYC'de İntravenöz glukagon ile özefagus ve özofagogastrik bileşkedeki düz kasların relaksasyonu sağlanarak yabancı cismin mideye geçişi sağlanabilir 2,21 . Özellikle sivri uçlu yabancı cisimlerde; aortoözefagial fistül ve perforasyon riski durumunda veya endoskopi ile yabancı cismin çıkartılmasının tehlikeli veya imkansız olduğu durumlarda cerrahi yöntem kaçınılmazdır.…”
Section: Tedavi Yöntemleriunclassified
“…A recent report found that a combination of glucagon (1 mg i.v.). an effervescent agent, and water to result in clearance of the food bolus in up to 69% of patients [31]. This con servative therapy seems to work less well with narrow rings.…”
Section: Therapymentioning
confidence: 99%